1998
DOI: 10.1046/j.1365-2648.1998.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of therapeutic touch on pain and anxiety in burn patients

Abstract: The purpose of this single-blinded randomized clinical trial was to determine whether therapeutic touch (TT) versus sham TT could produce greater pain relief as an adjunct to narcotic analgesia, a greater reduction in anxiety, and alterations in plasma T-lymphocyte concentrations among burn patients. Therapeutic touch is an intervention in which human energies are therapeutically manipulated, a practice conceptually supported by Rogers' (1970) theory of unitary human beings. Data were collected at a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 34 publications
(35 reference statements)
5
73
0
4
Order By: Relevance
“…Recent studies on cancer research suggest that instead of using other complementary and alternate medicine, cancer patients received highest benefit with energy medicine [15]. The concept of human bioenergy has its origin thousands of year back, till date many recent biofield therapies are in practice for their possible therapeutic potentials such as enhanced personal well-being in cancer patient [16], improved functional ability of arthritis patient [17], decreased pain and anxiety [18]. However, many other significant inhibitory effects on the cancer cell model have been published which suggest that biofield treatment could be a new and effective treatment approach for cancer [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on cancer research suggest that instead of using other complementary and alternate medicine, cancer patients received highest benefit with energy medicine [15]. The concept of human bioenergy has its origin thousands of year back, till date many recent biofield therapies are in practice for their possible therapeutic potentials such as enhanced personal well-being in cancer patient [16], improved functional ability of arthritis patient [17], decreased pain and anxiety [18]. However, many other significant inhibitory effects on the cancer cell model have been published which suggest that biofield treatment could be a new and effective treatment approach for cancer [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…It generates through internal physiological processes such as blood flow, brain and heart function, etc. Nowadays, many biofield therapies are in practice for their possible therapeutic potentials such as enhanced personal well-being, improved functional ability of arthritis patient, decreased pain and anxiety [10][11][12]. The practitioners of these therapy claim that the healers channel supraphysical energy and intentionally direct this energy towards target [13].…”
Section: Introductionmentioning
confidence: 99%
“…6 In burn patients, TT may decrease pain perception, reduce anxiety, and enhance immune function. 7 In several review articles and meta-analyses, clinical studies involving TT appeared to demonstrate clinical effects, but many studies, when evaluated as a whole, were considered to have weak experimental design and methodological limitations, such as questions about the appropriateness of the control group, the possible involvement of psychosocial factors, too small a N, etc. [8][9][10][11] Therefore, it can be concluded that there is a need for a large standard, randomized controlled trial of TT's efficacy.…”
mentioning
confidence: 99%